A high amylase‐producing bacterial strain exhibiting the phosphorus‐dissolving ability, isolated from freshwater aquaculture pond. (9th July 2020) - Yang, Qinglin; Luo, Lijun; Jiang, Yanhong; Zhang, Jiaojiao; Tang, Xiaoqi; Jiang, Mi; Wu, Zhengli; Li, Yanhong
Abstract: Amylase‐producing bacteria could improve water quality contaminated by waste from feed residue and fish metabolism, thereby increasing the efficiency of aquaculture systems. The objective of this research was to screen and optimize fermentation conditions of a high amylase‐producing strain. Four amylase‐producing bacterial strains (named S458‐1, G05, H38 and B09) were isolated from a grass carp pond, and the strain S458‐1 showed the highest amylase‐producing ability, with 19.58 ± 0.38 mm hydrolysis circle diameter. The strain S458‐1 was identified as Bacillus cereus based on morphological identification, biochemical identification and 16S rDNA sequence analysis. The optimal culture medium formula included (in g/L) Ca 2+ 0.8, Mg 2+ 0.2, Mn 2+ 0.4, Fe 2+ 0.6, Al 3+ 0.2, 1% soluble starch and 1% peptone. The optimal fermentation conditions were determined as initial pH 9, culture temperature 37°C, fermentation time of 60 hr and 2% inoculum. Under the optimal formula and condition, its enzyme activity increased from 32 U/ml to 173.01 U/ml, a 5.41‐fold increase. Surprisingly, our research found that the strain S458‐1 also had phosphorus degradation capabilities. Its phosphorus‐dissolving ability was both time‐ and concentration‐dependent. Thus, this study will make a contribution to the bacterial amylase based on the fermentation process and provide a theoretical basis for further research of aquatic probiotics.